Frequent and prolonged hospitalizations: A risk factor for early mortality in sickle cell disease patients - Houston‐Yu, Patricia; Rana, Sohail R.; Beyer, Betsy; Castro, Oswaldo (American journal of hematology, 2003)
A subset of patients with sickle cell disease (SCD) has frequent and prolonged hospitalizations. Clinical outcomes for this subset of patients are not known. We analyzed mortality data in 71 such patients enrolled in a case management study. Adult patients (mean age 32 years) with SCD and ≥50 hospitalization days/year or ≥6 admissions/year were enrolled. Clinical and psychosocial data were obtained. During a mean 24‐month follow up, 11 of 71 patients died (15.5%). Patients who died had a higher mean number of hospitalization days in the year before study entry (116 vs. 40, P < 0.000008) and were also more depressed than those who survived (mean score 17.8 vs. 11.9, P = 0.031). Frequent and prolonged hospitalizations are a risk factor for early mortality in patients with SCD. Am. J. Hematol. 72:201–203, 2003. © 2003 Wiley‐Liss, Inc.